Personal vs. historical nostalgia: a division of emotions - Marchegiani, Chris (School of Marketing, Curtin Business School, 2009)
While previous studies have explored emotions in nostalgia in a "unified" view, a distinction between the emotions that may occur resulting from the specific type of nostalgia experienced has not been made. This study examines emotional responses of 806 respondents experiencing Personal or Historical Nostalgia with an experimental research design. Although some emotions are common between the groups some distinctly different emotions are found as a result of the type of nostalgia experienced. This research assists in clarifying the difference in respondent's reactions to the two nostalgic types and supports the postulation that the two appeals are distinctly different.